Wujud Kesantunan dan Makna Dasar Pragmatik Imperatif dalam Tuturan antar Mahasiswa Melayu Sambas di Fakultas Tarbiyah dan Ilmu Keguruan IAIN Pontianak - Muchammad Djarot (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2019)
Imperative politeness is one of the concerns in character education. This is becausepoliteness in speaking is part of pillars in character education. Based on the results of study,students from the Tarbiyah and Teacher Training Faculty, Institute Agama Islam Neger(IAIN) Pontianak showed a tendency to be less polite in speaking, this is evident fromthe imperative speeches they convey in their interactions between them. Meanwhile, thespeech language they use represents their personality, and becomes problematic becausethey are studying at the Tarbiyah Faculty and Teacher Training of IAIN Pontianak adnthey are prepared to be prospective teachers. Methodologically, this research is classifedas qualitative research with a pragmatic approach. In research, the data collection methodused is the referring method and the profcient method. The objects of the study wasSambas Malay students who study at the Teacher Training Faculty, Institute Agama IslamNeger (IAIN) Pontianak .